HYGINIE, SANITATION AND NUTRITION OF SNACKS IN THE CANTEEN - Rahayu, Tutiek; Fauzan, Aji Nur Nur; Pertiwi, Kartika Ratna (Kingdom: The Journal of Biological Studies, 2023)
The purpose of this study was to determine the sanitation hygiene of the school canteen, the contribution of wet snack food to meeting the daily nutritional needs of students and to find out whether there were differences in sanitation and nutritional hygiene between wet snacks sold in the school canteen between Adiwiyata school canteens and non-Adiwiyata schools. This type of research is a descriptive observational research. The sample in this study is packaged and unpackaged snacks which are often sold in the school canteen. The variables in the study were the condition of the snacks in SD Adiwiyata and SD non-Adiwiyata in Bantul Regency. The standard instrument from the Indonesian Ministry of Health regarding hygiene, sanitation and nutritional content of food uses a computer application "nutry survey" and the E. coli test at the Microbiology Laboratory of the Faculty of Mathematics and Natural Sciences UNY. The result of the research is that the value of hygiene and sanitation of SD Adiwiyata canteen is 81.43% with good criteria, while non-Adiwiyata elementary school is 68.81% with moderate criteria. The average energy adequacy per day is 1461.6 kcal, while the recommended energy adequacy is 1594.5 kcal, thus only 92% fulfilled. There are differences in the hygiene and sanitation of wet snack food canteens between Adiwiyata and non-Adiwiyata elementary schools. Judging from the presence of E.coli and mold contamination, snacks in non-Adiwiyata school canteens showed that the number of E.coli and molds was higher than Adiwiyata Elementary School both in the morning and in the afternoon. Keywords : hygiene, sanitation, food nutrition, canteen